Factorize

  1) \ \   5xy+20x-9y-36    

     = 5x(y+4)-9(y+4)    

     = (y+4)(5x-9)    

   \\   

 2)  \ \    5ab-10b-7a+14    

     = 5b(a-2)-7(a-2)    

     = (a-2)(5b-7)    

   \\   

   3) \ \   9xy+7y-9y^2-7x    

     = 9y(x-y)-7(x-y)    

     = (x-y)(9y-7)    

   \\   

  4) \ \    3ax-6ay-8by+4bx    

     = 3a(x-y)+4b(x-y)    

     = (x-y)(3a+4b)    

   \\   

  5) \ \    4x^2-10xy-6xz+15yz    

     = 2x(2x-5y)-3z(2x-5y)    

     = (2x-5y)(2x-3z)    

   \\   

 6)   \ \   3ab-6bc-3ax+6cx    

     = 3b(a-2c)-3x(a-2c)    

     = (a-2c)(3b-3x)    

   \\   

  7)  \ \   a^2+ab(1+b)+b^3    

     = a^2+ab+ab^2+b^3    

     = a(a+b)+b^2 (a+b)    

     = (a+b)(a+b^2)    

   \\   

  8) \ \    xy^2+(x-1)y-1    

     = xy^2+xy-y-1    

     = xy(y+1)-1(y+1)    

     = (y+1)(xy-1)    

   \\   

 9)  \ \    b^2-ab(1-a)-a^3    

     = b^2-ab+a^2 b-a^3    

     = b(b-a)+a^2 (b-a)    

     = (b-a)(b+a^2)    

   \\   

 10)  \ \    y^2-y(2b+a)+2ab    

     = y^2-2yb-ya+2ab    

     = y(y-2b)-a(y-2b)    

     = (y-2b)(y-a)    

   \\   

   11)\ \    x-2-(x-2)^2+ax-2a    

     = (x-2)[1-(x-2)]+a(x-2)    

     = (x-2)(1-x+2-a)    

     = (x-2)(3-x-a)    

   \\   

  12)  \ \   x-1-(x-1)^2+4-4x    

     = (x-1)(1-(x-1))-4(x-1)    

     = (x-1)(1-x+1-4)    

     = (x-1)(-x-2)    

     = (1-x)(x+2)    

   \\   

  13)  \ \   b(c-d)^2-a(d-c)+5c-5d    

     = b(c-d)^2-a(d-c)+5(c-d)    

     = (c-d)[b(c-d)-a+5]    

     = (c-d)(bc-bd-a+5)    

   \\   

  14)  \ \   ab(c^2+b^2 )-a^2 cd-b^2 cd    

     = abc^2+abd^2-a^2 cd-b^2 cd    

     = ac(bc-ad)+bd(ad-bc)    

     = (bc-ad)(ac-bd)    

   \\   

 15)   \ \   ab(x^2+y^2 )+xy(a^2+b^2 )    

     = abx^2+aby^2+xya^2+xyb^2    

     = ax(bx+ay)+by(ay+bx)    

     = (bx+ay)(ax+by)    

   \\   

   16) \ \    ab(x^2+y^2 )-xy(a^2+b^2 )    

     = abx^2+aby^2-xya^2-xyb^2    

     = ax(bx-ay)+by(ay-bx)    

     = (bx-ay)(ax-by)    

   \\   

  17) \ \     (ax+by)^2+(bx-ay)^2    

      = a^2 x^2+b^2 y^2+2abxy+b^2 x^2+a^2 y^2-2abxy    

      = a^2 x^2+b^2 y^2+b^2 x^2+a^2 y^2    

      = a^2 (x^2+y^2 )+b^2 (x^2+y^2 )    

      = (x^2+y)(a^2+b^2)    

   \\   

  18) \ \     a(a+b+c)-bc    

      = a^2+ab-ac-bc    

      = a(a-c)+b(a-c)    

      = (a-c)(a+b)    

   \\   

  19) \ \     a(a-2b-c)+2bc    

      = a^2-2ab-ac+2bc    

      = a(a-c)-2b(a-c)    

      = (a-c)(a-2b)    

   \\   

  20)   \ \   3x^5-6x^4-2x^3+4x^2+x-2    

      = 3x^4 (x-2)-2x^2 (x-2)+(x-2)    

      = (x-2)(3x^4-2x^2+1)    

   \\   

   21) \ \    2a+2b-3cx-3bx+2c-3ax    

      = a(2-3x)+b(2-3x)+c(2-3x)    

      = (2-3x)(a+b+c)    

   \\   

 22)   \ \    a^2 b^2+b^2+a^2+1    

      = b^2 (a^2+1)+(a^2+1)    

      = (a^2+)(b^2+1)    

Advertisements